PENGARUH PENGGUNAAN ALAT PERAGA POP-UP BOOK TERHADAP HASIL BELAJAR MATERI TATA SURYA PADA SISWA KELAS VI SD INPRES JE’NETALLASA - Hidayatullah, Rezky; Nadrah; Said, Amin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the use of pop-up book teaching aids on student learning outcomes in the Solar System material. This study was motivated by the low student learning outcomes due to the dominance of conventional learning methods and the lack of use of interesting learning media. The type of research used was an experiment with a quasi-experimental design in the form of a non-equivalent control group design. The population of this study was all 49 sixth-grade students of SD Inpres Je'netallasa, with a sample consisting of class VI A as the control class and class VI B as the experimental class. Data collection techniques were carried out through tests (pretest and posttest), observation, and documentation. Data were analyzed using descriptive and inferential statistics with t-test tests. The results showed that the average pretest score of the experimental class was 55.48 and the control class was 57.12, which indicated that students' initial abilities were relatively the same. After being given treatment, the average posttest score of the experimental class increased to 82.35 and was in the completed category, while the control class obtained an average of 60.40 in the incomplete category. The results of the hypothesis test show a significance value of 0.001 < 0.05, so H₀ is rejected and H₁ is accepted. Thus, it can be concluded that the use of pop-up book teaching aids has a significant effect on student learning outcomes in the Solar System material.